Total Quality Management in Instruction and Teaching Effectiveness - Marites Bravo-Java (BIRCU, 2021)
The study on “Total Quality Management in Instruction and Teaching Effectiveness was conducted to assess the level of implementation of the Total Quality Management elements, such as leadership, student focus, faculty satisfaction, and programs/services management. The Total Quality Management index and its influence on the teaching effectiveness was also covered where the structured questionnaire for TQM and teaching effectiveness evaluation form were used. The respondents were chosen using complete enumeration among the Academic administrators and stratified random sampling among the faculty members. Descriptive statistics were used in describing the level of implementation of TQM elements and TQM index. The Multiple Regression Analysis was used to determine the relationship between the level of implementation of TQM elements and TQM index and its influence on teaching effectiveness. Results of the study revealed that there were high implementation of TQM elements and TQM index in the University of Southern Mindanao. Teaching effectiveness of the faculty members was rated by the students as very satisfactory. There was a significant relationship between the level of implementation of TQM elements and teaching effectiveness. Programs/services management came out as the best predictor of teaching effectiveness; where the higher the level of implementation of programs/services management, the more effective is the teaching at the University of Southern Mindanao.